Reasons for seeking orthodontic treatment in Lahore population: A cross-sectional survey in a low-income country - Faiz, Rasul; Muhammad, Waheed ul Hamid; Mehwish, Tariq; Zainab, Rizvi; Muhammad, Ilyas; Shabbir, Hussain Shah (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2019)
Introduction: Poor esthetics, dysfunction and discomfort are the key reasons for seeking orthodontic treatment across the world as reported by many researchers. This paper presents the causative factor for seeking orthodontic treatment in the patients who are visiting Punjab Dental Hospital of a populous city Lahore (de’ Montmorency College of Dentistry) in local settings and associating these reasons with demographic characteristics. Objective: Aim of this cross-sectional survey was to explore the reasons for seeking orthodontic treatment among individuals who are visiting PDH. Materials and methods: This study was carried out in Punjab Dental Hospital (PDH) after the approval of the Institutional Review Board (IRB) on a sample of 98 individuals having malocclusion assessed with Angle’s classification of the malocclusion. We chose simple random sampling. A self-structure questionnaire was designed to get data by the principal investigator after taking verbal and written consent. Descriptive statistics were calculated using SPSS 21. Chi-square test of association was applied to associate reasons with different demographic variables. P-value <0.05 was taken as significant. Results: Female respondents were more in number than males. Around one-third of respondents (30.6 %) had a monthly income of less than 25000 PKR ( 170). Esthetics was the primary reason for seeking orthodontic treatment. The most common type of malocclusion was the Class II malocclusion. Statistically significant factors that emerged in this study that turned into reasons for seeking orthodontic treatment were hurdles in marriage, referral by a general dentist, motivation by parents, self-esteem and speech problems. Conclusion: In conclusion, patients seek orthodontic treatment mainly to enhance facial esthetics and self-confidence, motivation by the parents, and social acceptability.